Answer:
x -2y -2=0
Step-by-step explanation:
using the formula, m= ( Y2 - Y1)/( X2-X1)
the gradient is found. the coordinates chosen are (2,0) and ( 0,-1)
the equation of the line is obtained using the formula
y -y1= m(x -x1)
Can't really see it, can you show it to me more?
Answer:
<h3>28</h3>
Step-by-step explanation:
Area of a square =
![s^2](https://tex.z-dn.net/?f=s%5E2)
Perimeter =
![4\times s](https://tex.z-dn.net/?f=4%5Ctimes%20s)
Where s = side
Solve for s using the area
![A =49\\\\49 = s^2\\\\Square\:root \:both\:sides\:of\:the\:equation\\\\\sqrt{49} = \sqrt{s^2} \\\\7 =s\\\\s =7](https://tex.z-dn.net/?f=A%20%3D49%5C%5C%5C%5C49%20%3D%20s%5E2%5C%5C%5C%5CSquare%5C%3Aroot%20%5C%3Aboth%5C%3Asides%5C%3Aof%5C%3Athe%5C%3Aequation%5C%5C%5C%5C%5Csqrt%7B49%7D%20%3D%20%5Csqrt%7Bs%5E2%7D%20%5C%5C%5C%5C7%20%3Ds%5C%5C%5C%5Cs%20%3D7)
Find the perimeter
![4\times s\\\\= 4 \times 7\\\\= 28](https://tex.z-dn.net/?f=4%5Ctimes%20s%5C%5C%5C%5C%3D%204%20%5Ctimes%207%5C%5C%5C%5C%3D%2028)
Answer:
![Y = (4,9)](https://tex.z-dn.net/?f=Y%20%3D%20%284%2C9%29)
Step-by-step explanation:
Given
![W(x_1,y_1) = (-5, 2)](https://tex.z-dn.net/?f=W%28x_1%2Cy_1%29%20%3D%20%28-5%2C%202%29)
![Z(x_4,y_4) = (-7, -3)](https://tex.z-dn.net/?f=Z%28x_4%2Cy_4%29%20%3D%20%28-7%2C%20-3%29)
![X(x_2,y_2) = (2, 4)](https://tex.z-dn.net/?f=X%28x_2%2Cy_2%29%20%3D%20%282%2C%204%29)
Required
Find Y
To do this, we make use of the mid-point formula
i.e.
![M = \frac{1}{2}(x_n+x_m,y_n+y_m})](https://tex.z-dn.net/?f=M%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28x_n%2Bx_m%2Cy_n%2By_m%7D%29)
WX and ZY are the diagonals of the parallelogram.
The mid-point of WX is:
![M = \frac{1}{2}(-5+2,2+4)](https://tex.z-dn.net/?f=M%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28-5%2B2%2C2%2B4%29)
![M = \frac{1}{2}(-3,6)](https://tex.z-dn.net/?f=M%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28-3%2C6%29)
The mid-point of ZY is:
![M = \frac{1}{2}(-7+x,-3+y)](https://tex.z-dn.net/?f=M%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28-7%2Bx%2C-3%2By%29)
Equate both values of M
![\frac{1}{2}(-3,6) = \frac{1}{2}(-7+x,-3+y)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28-3%2C6%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%28-7%2Bx%2C-3%2By%29)
Multiply both sides by 2
![(-3,6) = (-7+x,-3+y)](https://tex.z-dn.net/?f=%28-3%2C6%29%20%3D%20%28-7%2Bx%2C-3%2By%29)
By comparison:
![-7 + x = -3](https://tex.z-dn.net/?f=-7%20%2B%20x%20%3D%20-3)
![-3 + y = 6](https://tex.z-dn.net/?f=-3%20%2B%20y%20%3D%206)
![-7 + x = -3](https://tex.z-dn.net/?f=-7%20%2B%20x%20%3D%20-3)
![x = 7 -3](https://tex.z-dn.net/?f=x%20%3D%207%20-3)
![x = 4](https://tex.z-dn.net/?f=x%20%3D%204)
![-3 + y = 6](https://tex.z-dn.net/?f=-3%20%2B%20y%20%3D%206)
![y = 6 +3](https://tex.z-dn.net/?f=y%20%3D%206%20%2B3)
![y = 9](https://tex.z-dn.net/?f=y%20%3D%209)
Hence:
![Y = (4,9)](https://tex.z-dn.net/?f=Y%20%3D%20%284%2C9%29)